Study of the material composition of raw materials and the thermodynamic analysis of ore sulphidization - Burkitseterkyzy, G.; Katkeeva, G.L.; Oskembekov, I.M.; Gizatullina, D.R.; Zhunussov, A.M. (KSU Publ., 2017)
This research is aimed at a complex solution of two problems — increasing the efficiency of processing of oxidized copper ores and utilization of sulfur-containing waste from oil and gas processing. By the methods of chemical, mineralogical and granulometric analyzes the composition of the Sayak ore and waste sulfur was examined. It was found that the total copper content in the ore made 2.7 %, 1.8 % of which is represented by oxidized minerals. The main ore minerals are malachite, azurite, brochantite and chrysocolla. A thermodynamic analysis of the interaction of oxidized copper minerals with dissolved elemental sulfur possessing the properties of nanoparticles was carried out. The possibility in principle of copper sulfidization was established. Based on the obtained data on the thermodynamic properties of polysulfide systems, Δf H0 298.15, S0 298.15, Δf G0 298.15, Ср 0 298.15 of eight polysulfides — CaS2, CaS3, CaS4, CaS5, CaS6, CaS7, CaS8 и CaS9 were defined. The temperature dependences of the standard Gibbs energy of the reaction of dissolved sulfur with oxidized copper minerals — malachite, azurite, brochantite and chrysocolla — were defined. The possibility in principle of sulfidization of oxidized copper minerals with dissolved elemental sulfur possessing the properties of nanoparticles was established. It is shown that in the temperature range 298.15–500 K the formation of copper (II) sulfide and sulfur (IV) oxide in the interaction of oxidized copper minerals with elemental nano-sized sulfur is most likely. As the standard Gibbs energy of the sulfidation reaction increases, the minerals can be arranged in a row up to 400 K: azurite; malachite; brochantite; chrysocolla, after 400 K: azurite; brochantite; malachite; chrysocolla. In these rows, the probability of interaction with sulfur decreases.
Шикізаттың заттық құрамын зерттеу жəне кенді сульфидтеудің термодинамикалық талдауы
Изучение вещественного состава сырья и термодинамический анализ сульфидизации руды
Keywords: oxidized copper ore; sulfidization; polysulfides; sulfur-containing waste